Access for all : building inclusive financial systems - Helms, Brigit; Consultative Group to Assist the Poorest (Washington, DC : World Bank, 2006)
Building financial systems that works for the poor is the next great frontier of development and finance. This book gives some thoughtful and provocative ideas on how this can be achieved. It outlines the (3z(Bnew(3y (Bvision of microfinance, laying out in plain language what CGAP and others in the development field have learned over the past 10years about building inclusive financial systems.
"CGAP, Consultative Group to Assist the Poor."
Includes bibliographical references (p. 151-162) and index.
nmn 3/06/13, ijb 07/03/2019
Loans
Keywords: Microfinance; Credit; Financial institutions; Financial services industry; Poor; Microfinance